Mitochondrial Ndufa4l2 Enhances Deposition of Lipids and Expression of Ca9 in the TRACK Model of Early Clear Cell Renal Cell Carcinoma - Laursen, Kristian B.; Chen, Qiuying; Khani, Francesca; Attarwala, Nabeel; Gross, Steve S.; Dow, Lukas; Nanus, David M.; Gudas, Lorraine J. (Frontiers in Oncology, 2021)
Mitochondrial dysfunction and aberrant glycolysis are hallmarks of human clear cell renal cell carcinoma (ccRCC). Whereas glycolysis is thoroughly studied, little is known about the mitochondrial contribution to the pathology of ccRCC. Mitochondrial NDUFA4L2 is predictive of poor survival of ccRCC patients, and in kidney cancer cell lines the protein supports proliferation and colony formation. Its role in ccRCC however remains enigmatic. We utilized our established ccRCC model, termed Transgenic Cancer of the Kidney (TRACK), to generate a novel genetically engineered mouse model in which dox-regulated expression of an shRNA decreases NDUFA4L2 levels specifically in the renal proximal tubules (PT). This targeted knockdown of NDUFA4L2 reduced the accumulation of neutral renal lipid and was associated with decreased levels of the ccRCC markers carbonic anhydrase 9 (CA9) and Enolase 1 (ENO1). These findings suggest a link between mitochondrial dysregulation (i.e. high levels of NDUFA4L2), lipid accumulation and the expression of ccRCC markers ENO1 and CA9, and demonstrate that lipid accumulation and ccRCC development can potentially be attenuated by inhibiting NDUFA4L2.